Content analysis approach in critical discourse analysis of newspapers’ news - Agung Farid Agustian; Jenny Njaju Malik; Untung Yuwono (Center for Humanities and Innovation Studies, 2020)
This paper aims to explain how the content of the analysis can be used as a framework for investigating the ideologies contained in the text, especially in the reporting of the election. The problem in the current ideological discourse analysis is that there is no explicit and systematic method of explaining ideology and discourse criticism to be unscientific. The research question in this paper how the content analysis framework is presented in the news? How the content analysis framework consists of a content analysis framework leading to prescriptive objectives in the form of a news content unit? In this paper, research data were taken from the 2018 West Java governor election campaign news text from online newspapers. The results of the research were news content raised topics such as social actors, namely figure and groups, and social practice, namely politics, and social actions. The ideology presented in the news was an imbalance in terms of the frequency of reporting in the news. The imbalance result was related to asymmetric power ideology in the newspaper.